Head Impact Measurement Devices: A Clinical Review. (May 2016) - Williams, Richelle M.; Dowling, Margaret; O'Connor, Kathryn L.
Context: Concussive injuries are at the forefront of sports medicine research. Recently, researchers have used a variety of head- and helmet-based impact-monitoring devices to quantify impacts sustained during contact sport participation. This review provides an up-to-date collection of head accelerometer use at the youth, high school, and collegiate levels. Evidence Acquisition: PubMed was searched for articles published between 1980 and 2015 using the terms accelerometer and concussion, impact sensor and concussion, head impact telemetry system, head impact telemetry, and linear acceleration and concussion . An additional Google search was performed to capture devices without publications. Study Design: Clinical review. Level of Evidence: Level 4. Results: Twenty-four products track and/or record head impact for clinical or research use. Ten of these head impact devices have publications supporting their utility. Conclusion: Head impact measuring devices can describe athlete exposure in terms of magnitude and/or frequency, highlighting their utility within a multimodal approach for concussion assessment and diagnosis.